Etude de l'effet de degré de non-linéarité sur le Système VLC-OFDM - لمياء, ميدة; نجاح, بادي (University of El-Oued, 2022)
"Visible light Communications (VLC) is an emerging technology used to modulate visible light which will facilitate fundamentally in the world. Which will take advantage of the increasing popularity of solid lighting to open up many additional channels through which data can be transmitted, and because VLC needs high data rates, OFDM came as a solution because it is the most reliable and capable of sending high broadcast rates, high qualitative efficiency and short transmission time. Finally, we conducted a simulation study by calculating SNR and BER to determine the effect of the nonlinearity coefficient K on the VLC-OFDM system ""الاتصالات الضوئية المرئية (VLC)هي تقنية ناشئة تستخدم لتعديل الضوء المرئي والذي سيسهل بشكل اساسي في العالم. والذي سيستفيد من زيادة شعبية الإضاءة الصلبة لفتح العديد من القنوات الإضافية التي يمكن من خلالها نقل البيانات , ولان VLC تحتاج الى معدلات بيانات عالية جاءت OFDM كحل لانها الاكثرمصداقية و قادرة على الارسال معدلات بث عالية وكفاءة كيفية عالية ووقت ارسال قصير وفي الاخير, اجرينا دراسة محاكاة بحساب SNR و BER لتحديد تاثير معامل اللاخطية K على نظام VLC-OFDM "
مذكرات ماستر تخصص اتصالات
Keywords: ": visible light communications (VLC). Orthogonal Frequency Division (OFDM). "; "الاتصالات الضوئية المرئية(VLC) . مضاعفة تقسيم التردد المتعامد (OFDM) "